The wave-like movement of civilization - Johnson, Fred Emanuel (My University, 1899)
Introduction: As we step into the field of speculative philosophy, we are struck by the amazing number of ideas and opinions as to the significance and nature of civilization. Among these, we still find, at the present day, a feeling of doubt on the part of some as to whether civilization is a benefit or an evil to humanity. A few even take upon themselves to say that the evil tendencies seem to be gaining more rapidly than the good, and that they hide so much that has an elevating tendency. But we must bear in mind that the moral tendency constitutes only one of the many elements which are found to underlie all stages of civilization. Some of these others being intelligence, science, art, literature, and liberty. As all the individuals of any stage of civilization become more highly developed intellectually, physically, morally, and spiritually they as a whole and as individual members of this state of society have their capacity for doing good or evil increased in the same proportion as their degree of development in each of the great departments of human activity. Then, in order to counter act this tendency if such exist, there is a new field open to turn our forces into and see that each individual receives a proper training to fit him to enjoy the present civilization and that it shall in turn receive an element of strength from his existence.
Citation: Johnson, Fred Emanuel. The wave-like movement of civilization. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Civilization; Earlly Records; Egypt; Phoenicia; Chaldea; Assyria; Babylonia; Theses; Manuscripts (documents)